Serum cortisol concentrations during induced hypothermia for perinatal asphyxia are associated with neurological outcome in human infants. (January 2015) - Scaramuzzo, Rosa T.; Giampietri, Matteo; Fiorentini, Erika; Bartalena, Laura; Fiori, Simona; Guzzetta, Andrea; Ciampi, Mariella; Boldrini, Antonio; Ghirri, Paolo
Abstract Birth asphyxia is a cause of neonatal death or adverse neurological sequelae. Biomarkers can be useful to clinicians in order to optimize intensive care management and communication of prognosis to parents. During perinatal adverse events, increased cortisol secretion is due to hypothalamo–pituitary–adrenal axis activation. We aimed to investigate if cortisol variations during therapeutic hypothermia are associated with neurodevelopmental outcome. We compared 18 cases (neonates with birth asphyxia) with 18 controls (healthy term newborns) and confirmed increased serum cortisol concentrations following the peri-partum adverse event. Among cases, we stratified patients according to neurological outcome at 18 months (group A – good; group B – adverse) and found that after 24 h of therapeutic hypothermia serum cortisol concentration was significantly lower in group A vs group B (28.7 ng/mL vs 344 ng/mL, *p = 0.01). In group B serum, cortisol concentration decreased more gradually during therapeutic hypothermia. We conclude that monitoring serum cortisol concentration during neonatal therapeutic hypothermia can add information to clinical evaluation of neonates with birth asphyxia; cortisol values after the first 24 h of hypothermia can be a biomarker associated with neurodevelopmental outcome at 18 months of age.